2020
DOI: 10.18805/ijar.b-1307
|View full text |Cite
|
Sign up to set email alerts
|

The Expected Beneficial Effects of Watermelon Juice against Damage Induced by Gamma Radiation in the Testis of Rats

Abstract: Background: The present study was designed to evaluate the expected beneficial effect of watermelon juice (WJ) on γ-radiation induced inflammation and testes tissue damage in rats.Methods: The values for total phenolic contents, antioxidant activity and 2,2-diphenyl-1-picrylhydrazyl for WJ were detected. 28 Male rats were randomly divided into 4 groups (seven rats in each group) as follows; Control group, WJ group (received WJ by oral gavage 100 mg/kg B.Wt. / day/ 6 weeks), group 3 and 4: Irradiated group only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These compounds are used to treat a variety of illnesses, including renal impairment (Arthur et al, 2011;Hassan et al, 2019). The graviola extract's phytochemical analysis revealed many valuable secondary metabolites, such as tannins and steroids (El-Shahat et al, 2021). In numerous studies, GRV has been shown to protect against oxidative stress, enhance antioxidant enzymes such as catalase, superoxide dismutase, glutathione peroxidase, and glutathione, improve blood lipid levels, decrease LDL, total cholesterol, and triglycerides, increase HDL, and exert a wide range of beneficial effects, including anticonvulsive, anticancer, anti-arthritic, anti-malarial, hepatoprotective, and antidiabetic ones (Rady et al, 2018;Shukry et al, 2020;El-Shahat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds are used to treat a variety of illnesses, including renal impairment (Arthur et al, 2011;Hassan et al, 2019). The graviola extract's phytochemical analysis revealed many valuable secondary metabolites, such as tannins and steroids (El-Shahat et al, 2021). In numerous studies, GRV has been shown to protect against oxidative stress, enhance antioxidant enzymes such as catalase, superoxide dismutase, glutathione peroxidase, and glutathione, improve blood lipid levels, decrease LDL, total cholesterol, and triglycerides, increase HDL, and exert a wide range of beneficial effects, including anticonvulsive, anticancer, anti-arthritic, anti-malarial, hepatoprotective, and antidiabetic ones (Rady et al, 2018;Shukry et al, 2020;El-Shahat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The graviola extract's phytochemical analysis revealed many valuable secondary metabolites, such as tannins and steroids (El-Shahat et al, 2021). In numerous studies, GRV has been shown to protect against oxidative stress, enhance antioxidant enzymes such as catalase, superoxide dismutase, glutathione peroxidase, and glutathione, improve blood lipid levels, decrease LDL, total cholesterol, and triglycerides, increase HDL, and exert a wide range of beneficial effects, including anticonvulsive, anticancer, anti-arthritic, anti-malarial, hepatoprotective, and antidiabetic ones (Rady et al, 2018;Shukry et al, 2020;El-Shahat et al, 2021). Recent researches support the usefulness of GRV in the prevention of cancer and degenerative diseases, including renal disease, due to the presence of potent antioxidants such as polyphenols and flavonoids, which provide defense against the accumulation of reactive oxygen species (ROS) (Alam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%